EFFECT OF ORGANIC AND INORGANIC SOURCES OF NUTRIENT IN COMBINATION WITH SOIL AND FOLIAR APPLICATION OF ZINC IN RICE (Oryza sativa L.) - KUMAR, RAVI RANJAN; DAWSON, JOY; VERMA , ALOK KUMAR; TIWARI, DHANANJAY (The Bioscan, 2023)
The experiment consisted of ten treatments laid out in Randomised Block Design and replicated thrice with two factors viz Factor A: ZnSO4 at 15kg/ha, 25kg/ha and 0.5% foliar application at 30 and 60 DAT and Factor B: Organic manure at FYM 6t/ha, Vermicompost 2t/ha and Poultry manure 1980 kg/h. The significant and maximum value in growth parameters like number of tiller/hill (11.46), Plant dry weight (60.68 g), as well as yield attributes character like Number of grain/panicle (252.00), Test weight (33.03 g), and Grain yield (7.94 t/ha) was recorded maximum in Treatment 5 (90 kg N/ha + 2000 kg /ha VC + 25 kg/ ha ZnSO4 at Transplanting). the maximum B:C i.e. 2.72 was found treatment 5 i.e. 90 kg N/ha + 2000 kg /ha VC + 25 kg/ ha ZnSO4 at Transplanting which is followed by Treatment 3 (2.62) i.e.90 kg N/ha + 6 t/ha FYM + 15 kg/ha ZnSO4 at Transplanting).